Using BIM for the development of accessibility - Kładź, Magdalena; Borkowski, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
Accessibility in today's reality is becoming an increasingly important issue as it affects every individual. We are observing the progressive ageing of the Polish population. By applying the principles of universal design, all needs related to mobility, vision, hearing, and other issues are met, thereby creating inclusive spaces that eliminate social exclusion and enhance the quality of life. This article aims to demonstrate the usefulness of BIM in building urban accessibility. For this purpose, a point cloud acquired from laser scanning of a single-family building was utilised. Based on this, a digital BIM model of the actual building was created in Revit and subsequently modernised. This modernisation aimed to remove barriers from the building, as stipulated in the relevant regulation. The paper refers to the theory of ageing in place, a response to the steady increase in average age. The BIM model is not merely a geometric representation of the building, but a digital reconstruction of the object using elements equivalent to those used in reality, allowing for efficient data management.